Enhancement of ultracold molecule formation by local control in the nanosecond regime - J L Carini; S Kallush; R Kosloff; P L Gould (New Journal of Physics, 2015)
We describe quantum simulations of ultracold ^87 Rb _2 molecule formation using photoassociation (PA) with nanosecond-time-scale pulses of frequency chirped light. In particular, we compare the case of a linear chirp to one where the frequency evolution is optimized by local control (LC) of the phase, and find that LC can provide a significant enhancement. The resulting optimal frequency evolution corresponds to a rapid jump from the PA absorption resonance to a downward transition to a bound level of the lowest triplet state. We also consider the case of two frequencies and investigate interference effects. The assumed chirp parameters should be achievable with nanosecond pulse shaping techniques and are predicted to provide a significant enhancement over recent experiments with linear chirps.